Screening and characterization of endophytic fungi as antagonistic agents toward Fusarium oxysporum on eggplant (Solanum melongena) - FAJAR RAHMAH NURAINI; RATNA SETYANINGSIH; ARI SUSILOWATI (Society for Indonesian Biodiversity, 2017)
Nuraini FR, Setyaningsih R, Susilowati A. 2017. Screening and characterization of endophytic fungi as antagonistic agents toward Fusarium oxysporum on eggplant (Solanum melongena). Biodiversitas 18: 1377-1384. Fusarium oxysporum is a soil borne pathogenic fungus that causes wilt disease in members of the family Solanaceae including the eggplant (Solanum melongena L.). One approach to resolving the problem of wilt disease in eggplant is to find endophytic microbes with antagonistic activity against F. oxysporum. The study reported here aimed to isolate such endophytic fungal antagonists from growing eggplants, to determine their antagonistic mechanisms, and to identify them. Samples of pathogenic fungi from diseased plants, assumed to be F. oxysporum, were obtained from the Laboratory of Plant Pests and Diseases of the Faculty of Agriculture, Universitas Sebelas Maret Surakarta. These were used to evaluate the antagonistic potential of endophytic fungi obtained from healthy eggplants in Dawung Village, Matesih, Karanganyar, Central Java. Specimens of various plant parts were collected from the healthy eggplants. The surfaces of these samples were sterilized for four minutes to remove contaminants, and then crushed excisions were cultured on a potato dextrose agar (PDA) medium. Antagonistic tests between endophytic and pathogenic fungi used the agar plug diffusion technique. Identification of fungi isolates was carried out on the basis of morphological characteristics. Six endophytic fungi isolated had antagonist activity against F. oxysporum. The antagonistic mechanism of FEB1, FEB2, FEB5 and FED1 was competition; FED2 was antibiosis, and FED3 was parasitism. Based on their morphological characteristics, FEB2, FEB5 and FED3 were identified as Helicomyces spp.; FEB1 was a Rhizopus sp.; FED1 was a Mucor sp.; and FED2 was a species of Penicillium.